Bimodal distribution of wind pressure on windward facades of high-rise buildings induced by interference effects. Issue 200 (May 2020) - Liang, Q.S.; Fu, J.Y.; Li, Z.; Yan, B.W.; Shu, Z.R.; He, Y.C.
Abstract: Understanding the characteristics of wind pressures on structural façades is of great importance for wind-resistant design of claddings and glass curtains of buildings. This article presents some interesting findings about the behavior of wind pressure on the façades of a high-rise building influenced by an interference building via wind tunnel tests. The bimodal probability distribution (BPD) of wind pressure acting on the windward side of the principal building is highlighted, which has been rarely reported and investigated in previous studies. This BPD featured wind pressure consists of both positive and negative components that alternate along time in a consistent way to the vortex shedding downwind of the interference building. By changing the relative position between the principal building and interference building, it is observed that the bimodal distribution can be transformed to a unimodal form, mostly with a long tailed on the left-hand-side of the probability-density-function (PDF). Based on the above findings, this study proposes a mixture PDF model which is actually a combination of the Gaussian model and the generalized-extreme-value (GEV) model. While the Gaussian PDF accounts for the component dominated by the background approaching flows, the GEV one is associated with the aerodynamic interference effects. Parametric analysis is then conducted for the BPD feature based on the proposed mixture model, and detailed process for the transformation of different PDF patterns (from varied bimodal patterns to both Gaussian and tailed unimodal statuses) is reproduced. The findings can provide useful insights for the wind-resistant design of claddings and curtain walls of high-rise buildings, and for further analyzing non-Gaussian characteristics of wind pressure, such as for estimating extreme pressure values. Highlights: Phenomenon of bimodal probability distribution (BPD) of wind pressure on windward side of high-rise buildings is observed. BPD-featured pressure consists of both positive and negative components that alternate along time at a certain frequency. A mixture PDF model is proposed for BPD featured wind pressure. Conversion between BPD process and Gaussian process is explored.